Introduction to four reviews addressing critical topics identified by the 2015 Nurse Practitioner Research Agenda Roundtable: Priorities for policy, workforce, education, and practice. Issue 12 (December 2018) - Buchholz, Susan W.; Klein, Tracy; Cooke, Cindy; Cook, Michelle L.; Knestrick, Joyce; Dickins, Kirsten
ABSTRACT: Background and Purpose: In 2015, an invitational think tank was convened by the Fellows of the American Association of Nurse Practitioners to update the 2010 Nurse Practitioner (NP) Research Agenda Roundtable. This effort was undertaken to provide guidance for future health care research. The purpose of this article is to introduce the process used for conducting four reviews that address critical topics related to specific research priorities emanating from the 2015 NP Research Agenda Roundtable. The four reviews are published in this issue of Journal of the American Association of Nurse Practitioners (JAANP) to address the state of current research relevant to NP policy, workforce, education, and practice. Methods: This introductory article provides an overview of the systematic process used to evaluate the four topical area. The type of review selected, the search strategy, critical appraisal, data extraction, and data synthesis will be further described in the four review articles. Conclusions: Four reviews that examine literature regarding specific aims important to NPs will address strengths as well as gaps in the literature. Implications for Practice: The knowledge offered by the four reviews has the potential to inform future research, which will benefit NPs and other health care stakeholders.